IEO Annual Report 2013. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2013)
The Independent Evaluation Office (IEO) evaluation on International Reserves: IMF Concerns and Country Perspectives was discussed by the Board in December 2012. This evaluation examined the IMF's analysis of the effect of reserves on the stability of the international monetary system and its advice on reserve adequacy assessments in the context of bilateral surveillance. In the multilateral context, the evaluation acknowledged the IMF's broader work stream on the international monetary system but noted that this work had not sufficiently informed the analysis and recommendations regarding reserves. The IEO evaluation of The Role of the IMF as Trusted Advisor was discussed by the Board in February 2013. This evaluation found that perceptions of the IMF had improved, but that they varied markedly by region and country type. Recognizing that there will always be an inherent tension between the IMF's roles as a global watchdog and as a trusted advisor to member country authorities, the evaluation report explored how the IMF could sustain the more positive image it had achieved in the aftermath of the recent global crisis. The evaluation found that among key challenges facing the IMF were improving the value added and relevance of IMF advice and overcoming the perception of a lack of even-handedness.